Replacement of severely traumatized teeth with immediate implants and immediate loading: literature review and case reports. Issue 6 (14th July 2015) - Sheng, Lieping; Silvestrin, Tory; Zhan, Jing; Wu, Liqun; Zhao, Qirong; Cao, Zheng; Lou, Zhifeng; Ma, Qingfang
Abstract: One of the options for management of severely traumatized dentitions is to provide immediate implant placement with immediate loading. Three representative cases out of 15 patients with 23 traumatized teeth treated to date in our clinic are presented. None had labial bone fractures. The teeth were replaced with NobelReplace Groovy implants (Nobel Biocare, Gothenburg, Sweden) in the fresh sockets immediately after extraction. They were placed toward the palatal areas in the sockets and 3 mm below the gingival margins. If there were gaps between implants and sockets wider than 1 mm, particulate deproteinized bovine bone was grafted in the gaps. Immediately after placement, the implants were loaded with provisional prostheses. The final restorations were installed 3–4 months later. The patients were reevaluated clinically and radiographically 1–3 years after the final restorations had been placed. In all 15 patients, excellent functional and esthetic results were achieved. No implants showed radiolucency, peri‐implant suppuration, or mobility. The patients were satisfied with the results. Immediate implant placement with immediate loading is an option that provides good treatment outcomes and allows good functional and esthetic results, as well as addressing the social/psychological aspects of dental trauma.